Infringement nation copyright 2.0 and you - Tehranian, John. (New York ; Oxford : Oxford University Press, 2011)
Written on the occasion of copyright's 300th anniversary, John Tehranian's book presents an engaging and accessible analysis of the history and evolution of copyright law and its profound impact on the lives of ordinary individuals in the 21st century.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Copyright -- United States